Dual-conductivity positive electrode active material, preparation method thereof and lithium ion battery
By constructing a cladding layer of polyimide and carbon nanotubes on the surface of lithium-rich manganese-based materials, the problem of instability of the surface structure of the material is solved, the electrochemical performance of high magnification and long cycles is achieved, and the electrochemical performance and cycle life of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202510381710.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-07-04
AI Technical Summary
In the prior art, the surface structure of the lithium-rich manganese-based material is unstable, resulting in low first-time Coulomb efficiency, poor rate performance and severe post-cycle voltage and capacity attenuation in lithium-ion batteries, and lacks a variety of methods to improve the electrochemical performance of the material.
A cladding layer consisting of polyimide and carbon nanotubes is used to construct a nano-level cladding layer in situ on the surface of lithium-rich manganese-based materials. Polyimide provides ion-conducting channels and mechanical support, and carbon nanotubes provide electron-conducting channels and structural stability, and regulate the mass ratio of the two to 1-10:0.1-1 to form a uniform continuous cladding layer.
It significantly improves the conductivity, structural stability, interface stability and thermal stability of lithium-rich manganese-based materials, improves its electrochemical performance and cyclic performance, and improves the charge and discharge performance and cycle life of the materials.
Smart Images

Figure CN120261529A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and particularly relates to a dual-conductive cathode active material, a preparation method thereof, and a lithium-ion battery. Background Art
[0002] With the rapid development of power equipment such as electric vehicles and energy storage power stations, the demand for high-energy-density lithium-ion batteries is increasing day by day. The lithium-rich manganese-based material (xLi2MnO3·(1-x)LiMO2; where 0≤x≤1, and M includes at least one of Ni, Co, and Mn) has advantages such as high specific capacity (>250 mAh·g -1 ), low cost, and high safety, and is considered to be the key cathode active material for lithium-ion batteries to achieve high specific energy (>350 Wh·kg -1 ).
[0003] The Li2MnO3 phase and lattice oxygen of the lithium-rich manganese-based material participate in the electrochemical reaction, making it have a higher capacity. However, this also causes the surface crystal phase structure to change from a layered structure to a spinel / rock salt phase, resulting in the release of component lattice oxygen, the dissolution of transition metals, and the formation of an inert impurity layer, thus causing many problems in the lithium-rich manganese-based material. For example, the initial Coulomb efficiency is low, the rate performance is poor, and the voltage and capacity decay severely after cycling, which limits its development in lithium-ion batteries.
[0004] In the prior art, surface modification technology is often used to stabilize the surface structure of the lithium-rich manganese-based material, inhibit the side reaction at the electrode / electrolyte interface, and effectively improve the electrochemical performance of the lithium-rich manganese-based material. Commonly used surface modification methods include in-situ construction of a surface inert layer (such as MgO), an active layer (such as MnO2), an electronic conduction layer (such as a nano-carbon material), and an ionic conduction layer (such as LiFePO4); among them, the inert layer can only improve the structural stability, the active layer can only improve the electrochemical reaction, the electronic conduction layer can only promote electronic conduction, and the ionic conduction layer can only promote ionic conduction. Different surface coating layers correspond to single functions, which can improve the single performance of the lithium-rich manganese-based material, but lack the multi-effect synergy advantage and cannot improve the electrochemical performance of the material in multiple aspects, which is not conducive to industrial promotion.
[0005] Therefore, how to effectively optimize and modify the lithium-rich manganese-based material to obtain a dual-conductive (ionic and electronic conduction) cathode active material and further improve its capacity, rate performance, and cycle performance is one of the technical problems that need to be solved urgently in this field. Summary of the Invention
[0006] In view of this, the present invention provides a dual-conductive cathode active material to improve the capacity, rate performance, and cycle performance of the lithium-rich manganese-based material.
[0007] In a first aspect, the present invention provides a dual-conductive cathode active material, comprising a matrix material and a coating layer coated on the outer surface of the matrix material. The matrix material is a lithium-rich manganese-based material, and the coating layer comprises polyimide and carbon nanotubes;
[0008] The mass ratio of the polyimide to the carbon nanotubes is 1-10:0.1-1.
[0009] In an optional embodiment, the mass ratio of the coating layer to the matrix material is 0.1-10:1-100.
[0010] In an optional embodiment, the thickness of the coating layer is 0.1 nm - 20 nm.
[0011] In an optional embodiment, the carbon nanotubes include at least one of single-walled carbon nanotubes, double-walled carbon nanotubes, hydroxylated multi-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes, and aminated multi-walled carbon nanotubes.
[0012] In an optional embodiment, the chemical formula of the lithium-rich manganese-based material is xLi2MnO3·(1-x)LiMO2; wherein, 0 ≤ x ≤ 1, and M includes at least one of Ni, Co, and Mn.
[0013] In a second aspect, the present invention provides a method for preparing the above dual-conductive cathode active material, comprising the following steps:
[0014] (1) Reacting carbon nanotubes with a dianhydride, a diamine, and / or a polyamine to obtain a polyamic acid / carbon nanotube dispersion;
[0015] (2) Placing the lithium-rich manganese-based material in the polyamic acid / carbon nanotube dispersion, stirring, filtering, drying the filter residue, and performing heat treatment to obtain the product.
[0016] In an optional embodiment, the molar ratio of the dianhydride to the diamine and / or the polyamine is 1:0.95-1.05.
[0017] In an optional embodiment, the proportional relationship between the dianhydride and the carbon nanotubes is 0.0001 mol - 0.01 mol:0.05 g - 1.5 g.
[0018] In an optional embodiment, the proportional relationship between the dianhydride and the lithium-rich manganese-based material is 0.0001 mol - 0.01 mol:8 g - 180 g.
[0019] In an optional embodiment, the solid content of the polyamic acid / carbon nanotube dispersion is 0.01 wt% - 10 wt%.
[0020] In an alternative embodiment, the step (1) further includes a solvent, and the solvent includes at least one of N-N-dimethylformamide, N-N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0021] In an alternative embodiment, the ratio of the dianhydride to the solvent is 0.0001 mol - 0.01 mol: 8 g - 960 g.
[0022] In an alternative embodiment, the reaction time is 2 h - 24 h.
[0023] In an alternative embodiment, the stirring time is 10 min - 120 min.
[0024] In an alternative embodiment, the temperature of the heat treatment is 200°C - 400°C, and the treatment time is 15 min - 300 min.
[0025] In an alternative embodiment, the dianhydride includes at least one of pyromellitic dianhydride, biphenyl dianhydride, hexafluoroisopropyl phthalic anhydride, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-terphenyltetracarboxylic dianhydride, diphenyl sulfide dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, and bisphenol A dianhydride;
[0026] In an alternative embodiment, the diamine includes at least one of benzidine disulfonic acid, bis(4-aminophenyl) sulfide, 5,5'-diamino-2,2'-hydroxy-biphenyl, 2,2'-bis(3-amino-4-hydroxyphenyl) propane, 3,3'-diamino-4,4'-dihydroxybiphenyl, 3,5-diaminobenzoic acid, 3,5-bis(4-aminophenoxy) benzoic acid, 5,5'-oxybis(2-aminophenol), and aminopropyl-terminated polydimethylsiloxane;
[0027] In an alternative embodiment, the polyamine includes at least one of 1,3,5-tris(4-aminophenoxy) benzene, 1,3,5-tris(4-aminophenyl) benzene, 1,3,5-tris(2-amino-4-carboxyphenyl) benzene, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, and 1,3,5-triaminobenzene.
[0028] In a third aspect, the present invention provides a lithium-ion battery, including a positive electrode, the positive electrode includes a positive electrode active layer, and the positive electrode active layer includes a positive electrode active material; the positive electrode active material includes the above-mentioned dual-conductive positive electrode active material.
[0029] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0030] 1. The dual-conductive cathode active material provided by the present invention comprises a matrix material and a coating layer coated on the outer surface of the matrix material. The matrix material is a lithium-rich manganese-based material, and the coating layer comprises polyimide and carbon nanotubes; the mass ratio of the polyimide to the carbon nanotubes is 1-10:0.1-1. The dual-conductive cathode active material provided by the present invention has good ion and electron conduction capabilities, ensuring good charge-discharge performance and cycle life of the cathode active material; specifically: on the one hand, polyimide has excellent high-temperature resistance, and the thermal decomposition temperature > 450 °C, which can provide an ion conduction channel and ensure the thermal stability of the cathode active material, guaranteeing the safety performance of the battery; on the other hand, polyimide has extremely high adhesion strength and adheres to the surface of the matrix material in the form of a polyamic acid precursor, thereby in-situ forming chemical bonds, ionic bonds, covalent bonds, and van der Waals forces on the surface of the matrix material, and then forming a polyimide layer with high strength through high-temperature imidization, playing a role in stabilizing the surface structure of the matrix material; thirdly, polyimide also has abundant lithium-ion complexing sites, and the polyimide structure contains ion-conductive diamines and / or polyamines, which is beneficial to improving the migration rate of lithium ions in the cathode active material and ensuring the performance of the battery capacity. In addition, the addition of carbon nanotubes can greatly improve the penetration ability of the electrolyte in the cathode active material and promote ion conduction; at the same time, carbon nanotubes also have good electronic conductivity, and the fibrous structure of carbon nanotubes can form a continuous conductive network in the matrix material, providing an electron conduction channel and ensuring strength, effectively stabilizing the surface structure of the matrix material; after adding carbon nanotubes, the cathode active material has higher toughness, can improve the exfoliation caused by the volume change of the material during the charge-discharge process, improve the rate performance and cycle life, and promote the performance of the cathode active material capacity;
[0031] By regulating the mass ratio of polyimide to carbon nanotubes to be 1-10:0.1-1, the present invention can prepare a uniform and continuous coating layer of polyimide and carbon nanotubes. This coating layer combines the excellent mechanical stability, chemical stability, and thermal stability of polyimide materials, and also has the excellent electrical conductivity, thermal conductivity, and toughness of carbon nanotubes, promoting the performance of the cathode active material capacity and improving the rate and cycle performance. If there is too much polyimide, it is not conducive to the uniform coating of the coating layer on the surface of the lithium-rich manganese-based material, and the formed coating layer is relatively thick, causing large polarization and affecting the performance of the capacity; if the mass of carbon nanotubes is too much, it is impossible to ensure the formation of a continuous coating layer on the surface of the lithium-rich manganese-based material, and the formed coating layer is too thin to protect the surface structure of the lithium-rich manganese-based material;
[0032] In summary, the coating layer of the present invention includes polyimide and carbon nanotubes, which can not only maintain the conductivity of the carbon nanotubes, but also prevent the agglomeration of the carbon nanotubes based on the semi-insulating property of the polyimide, optimize the conductive network, and improve the conductivity; the polyimide provides mechanical support, and the carbon nanotubes enhance the toughness of the material, improving the structural stability of the coating layer; at the same time, the polyimide provides chemical stability, and the carbon nanotubes enhance the interfacial conductivity, improving the interfacial stability of the cathode active material; in addition, the polyimide has thermal stability, and the carbon nanotubes enhance the thermal conductivity, further improving the thermal stability of the material. In summary, based on the synergistic effect of polyimide and carbon nanotubes, the coating layer significantly improves the conductivity, structural stability, interfacial stability, electrochemical performance and thermal stability of the lithium-rich manganese-based material, and can stabilize the surface structure of the matrix material.
[0033] 2. The preparation method of the dual-conductive cathode active material provided by the present invention constructs a nanoscale coating layer in situ on the surface of the matrix material to achieve high-rate and long-cycle electrochemical performance; at the same time, the preparation method of the present invention is simple and can be produced on a large scale.
[0034] 3. The preparation method of the dual-conductive cathode active material provided by the present invention directly reacts a dianhydride, a diamine and / or a polyamine, and carbon nanotubes, which can improve the dispersion of the carbon nanotubes, is conducive to the formation of a uniform and continuous conductive path inside the polyimide thin layer, ensuring conductivity, and also increasing the structural stability of the coating layer, preventing the coating from breaking caused by uneven stress dispersion.
[0035] 4. The preparation method of the dual-conductive cathode active material provided by the present invention selects solvents including at least one of N-N-dimethylformamide, N-N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone. The obtained polyimide is oily, has good long-term stability, does not swell in the electrolyte, has good high-temperature resistance, contains an ion-conducting structure, improves the ion migration rate, and in-situ fuses the carbon nanotubes to ensure conductivity. Description of the Drawings
[0036] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for use in the description of the specific embodiments or the prior art. Obviously, the following drawings are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0037] Figure 1 It is a transmission electron microscope image of the dual-conductive cathode active material prepared in Example 1 of the present invention;
[0038] Figure 2 It is a transmission electron microscope image of the dual-conductive cathode active material prepared in Example 2 of the present invention;
[0039] Figure 3 It is the transmission electron microscope image of the dual-conductive positive electrode active material prepared in Example 3 of the present invention;
[0040] Figure 4 It is the scanning electron microscope image of the dual-conductive positive electrode active material prepared in Example 2 of the present invention;
[0041] Figure 5 It is the scanning electron microscope image of the lithium-rich manganese-based material of the present invention;
[0042] Figure 6 It is the XRD pattern of the dual-conductive positive electrode active material and the lithium-rich manganese-based material prepared in Example 1 of the present invention;
[0043] Figure 7 It is the charge-discharge curve of the dual-conductive positive electrode active material and the lithium-rich manganese-based material prepared in Example 2 of the present invention after one cycle at a current density of 0.1C (1C = 200 mAh g -1 );
[0044] Figure 8 It is the rate performance test result of Example 2 of the present invention and the lithium-rich manganese-based material at different current densities. Detailed implementation manners
[0045] The following embodiments are provided to better further understand the present invention. They are not limited to the best implementation manner, and do not limit the content and protection scope of the present invention. Any product that is the same as or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior art features falls within the protection scope of the present invention.
[0046] For those not specifying specific experimental steps or conditions in the embodiments, the operations or conditions of the conventional experimental steps described in the literature in this field can be followed. For those reagents or instruments not specifying the manufacturer, they are all conventional reagent products that can be obtained through commercial purchase.
[0047] To solve the problems existing in the above-mentioned related technologies, according to the first aspect of the present invention, the present invention provides a dual-conductive positive electrode active material, which includes a matrix material and a coating layer coated on the outer surface of the matrix material. The coating layer includes polyimide and carbon nanotubes with a mass ratio of 1-10:0.1-1; the matrix material is a lithium-rich manganese-based material; the carbon nanotubes include at least one of single-walled carbon nanotubes, double-walled carbon nanotubes, hydroxylated multi-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes, and aminated multi-walled carbon nanotubes; the mass ratio of the coating layer to the matrix material is 0.1-10:1-100; the thickness of the coating layer is 0.1 nm - 20 nm; the chemical formula of the lithium-rich manganese-based material is xLi2MnO3·(1 - x)LiMO2; wherein, 0 ≤ x ≤ 1, and M includes at least one of Ni, Co, and Mn.
[0048] The dual-conductive cathode active material provided by the present invention has good ion and electron conduction capabilities, can stabilize the surface structure of the matrix material, and ensure good charge-discharge performance and cycle life of the cathode active material. Specifically, on the one hand, polyimide has excellent high-temperature resistance, with a thermal decomposition temperature > 450 °C, which can provide ion-conducting channels and ensure the thermal stability of the cathode active material, thus ensuring the safety performance of the battery. On the other hand, polyimide has extremely high adhesive strength and adheres to the surface of the matrix material in the form of a polyamic acid precursor, thereby in-situ forming chemical bonds, ionic bonds, covalent bonds, and van der Waals forces on the surface of the matrix material. After high-temperature imidization, a polyimide layer with high strength is formed, which plays a role in stabilizing the surface structure of the matrix material. Thirdly, polyimide also has abundant lithium-ion complexing sites, and the polyimide structure contains ion-conductive diamines and / or polyamines, which is beneficial to improving the migration rate of lithium ions in the cathode active material and ensuring the battery capacity. In addition, the addition of carbon nanotubes can greatly improve the penetration ability of the electrolyte in the cathode active material and promote ion conduction. At the same time, carbon nanotubes also have good electronic conductivity, and the fibrous structure of carbon nanotubes can form a continuous conductive network in the matrix material, providing electron-conducting channels and ensuring strength, effectively stabilizing the surface structure of the matrix material. After adding carbon nanotubes, the cathode active material has higher toughness, can improve the peeling caused by the volume change of the material during charge and discharge, improve the rate performance and cycle life, and promote the capacity of the cathode active material.
[0049] By regulating the mass ratio of polyimide to carbon nanotubes to be 1-10:0.1-1, the present invention can prepare a uniform and continuous polyimide and carbon nanotube coating layer. This coating layer combines the excellent mechanical stability, chemical stability, and thermal stability of polyimide materials, and also has the excellent electrical conductivity, thermal conductivity, and toughness of carbon nanotubes, promotes the capacity of the cathode active material, and improves the rate and cycle performance. If there is too much polyimide, it is not conducive to the uniform coating of the coating layer on the surface of the lithium-rich manganese-based material, and the formed coating layer has a large thickness, resulting in large polarization and affecting the capacity. If the mass of carbon nanotubes is too much, it is impossible to ensure the formation of a continuous coating layer on the surface of the lithium-rich manganese-based material, and the formed coating layer has too low a thickness to protect the surface structure of the lithium-rich manganese-based material.
[0050] In summary, the coating layer of the present invention includes polyimide and carbon nanotubes, which can not only maintain the conductivity of the carbon nanotubes, but also prevent the aggregation of the carbon nanotubes based on the semi-insulating property of the polyimide, optimize the conductive network, and improve the conductivity; the polyimide provides mechanical support, and the carbon nanotubes enhance the toughness of the material, improving the structural stability of the coating layer; at the same time, the polyimide provides chemical stability, and the carbon nanotubes enhance the interfacial conductivity, improving the interfacial stability of the cathode active material; in addition, the polyimide has thermal stability, and the carbon nanotubes enhance the thermal conductivity, further improving the thermal stability of the material. In summary, based on the synergistic effect of the polyimide and the carbon nanotubes, the coating layer significantly improves the conductivity, structural stability, interfacial stability, electrochemical performance and thermal stability of the lithium-rich manganese-based material, and can stabilize the surface structure of the matrix material.
[0051] In a second aspect, the present invention provides a method for preparing a dual-conductive cathode active material, comprising the following steps:
[0052] (1) Obtaining a polyamic acid / carbon nanotube dispersion by subjecting carbon nanotubes, a dianhydride, a diamine and / or a polyamine to a condensation polymerization reaction for 2 h - 24 h; the dianhydride includes at least one of pyromellitic dianhydride, biphenyl dianhydride, hexafluoroisopropyl phthalic anhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-terphenyltetracarboxylic dianhydride, diphenyl sulfide dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, bisphenol A type dianhydride; the diamine includes at least one of benzidine disulfonic acid, bis(4-aminophenyl) sulfide, 5,5'-diamino-2,2'-hydroxy-biphenyl, 2,2'-bis(3-amino-4-hydroxyphenyl) propane, 3,3'-diamino-4,4'-dihydroxybiphenyl, 3,5-diaminobenzoic acid, 3,5-bis(4-aminophenoxy) benzoic acid, 5,5'-oxybis(2-aminophenol), aminopropyl-terminated polydimethylsiloxane; the polyamine includes at least one of 1,3,5-tris(4-aminophenoxy) benzene, 1,3,5-tris(4-aminophenyl) benzene, 1,3,5-tris(2-amino-4-carboxyphenyl) benzene, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 1,3,5-triaminobenzene; a solvent is also included, and the solvent includes at least one of N-N-dimethylformamide, N-N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone; the solid content of the polyamic acid / carbon nanotube dispersion is 0.01 wt% - 10 wt%; the molar ratio of the dianhydride to the diamine and / or the polyamine is 1:0.95 - 1.05; the proportional relationship between the dianhydride and the carbon nanotubes is 0.0001 mol - 0.01 mol:0.05 g - 1.5 g; the proportional relationship between the dianhydride and the lithium-rich manganese-based material is 0.0001 mol - 0.01 mol:8 g - 180 g; the proportional relationship between the dianhydride and the solvent is 0.0001 mol - 0.01 mol:8 g - 960 g;
[0053] (2) The lithium-rich manganese-based active material is placed in the above polyamic acid / carbon nanotube dispersion liquid, stirred for 10 min - 120 min, and after suction filtration, drying, grinding, and sieving, it is subjected to high-temperature thermal imidization treatment at 200 °C - 400 °C for 15 min - 300 min to obtain the product.
[0054] In the present invention, a nanoscale coating layer is in-situ constructed on the surface of the lithium-rich manganese-based material to achieve high-rate and long-cycle electrochemical performance; meanwhile, the preparation method of the present invention is simple and can be produced on a large scale.
[0055] The present invention directly reacts a dianhydride, a diamine and / or a polyamine, and carbon nanotubes, which can improve the dispersibility of the carbon nanotubes, is beneficial to the formation of a uniform and continuous conductive path inside the polyimide thin layer by the carbon nanotubes, ensures the conductivity, and also increases the structural stability of the coating layer to prevent the coating layer from breaking due to uneven stress dispersion.
[0056] The present invention defines that the solvent includes at least one of N-N-dimethylformamide, N-N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone. The obtained polyimide is oily, has good long-term stability, does not swell in the electrolyte, has good high-temperature resistance performance, contains an ion-conducting structure, improves the ion migration rate, and in-situ fuses carbon nanotubes to ensure the conductivity.
[0057] The following further describes the present invention in detail with specific embodiments, and these embodiments should not be construed as limiting the scope claimed by the present invention.
[0058] Example 1
[0059] This example provides a preparation method of a dual-conducting cathode active material, including the following steps:
[0060] (1) 1.37 g of 4,4'-biphenyl ether dianhydride, 1.46 g of benzidine disulfonic acid, and 0.4 g of hydroxylated multi-walled carbon nanotubes are added to 50 g of N-methylpyrrolidone, and reacted for 4 h under a nitrogen atmosphere to obtain a polyamic acid / carbon nanotube dispersion liquid with a solid content of 6.07 wt%;
[0061] (2) 12 g of lithium-rich manganese-based material (0.8Li2MnO3·(0.2LiNiO2)) is added to the above polyamic acid / carbon nanotube dispersion liquid, stirred for 120 min, and after suction filtration, drying, grinding, and sieving, it is subjected to thermal imidization treatment at 300 °C for 120 min to obtain the product; wherein, the mass ratio of the coating layer to the lithium-rich manganese-based material is 1:5; in the coating layer, the mass ratio of polyimide to carbon nanotubes is 7:1, and the thickness of the coating layer is 8 nm.
[0062] Example 2
[0063] This embodiment provides a method for preparing a dual-conductive cathode active material, which is basically the same as the steps of Embodiment 1, except that in step (1), the mass of N-methylpyrrolidone is 300 g, the solid content of the polyamic acid / carbon nanotube dispersion is 1.07 wt%, and the mass ratio of the coating layer to the lithium-rich manganese-based material is 1:4; in the coating layer, the mass ratio of polyimide to carbon nanotubes is 4.8:0.3, and the thickness of the coating layer is 10 nm.
[0064] Example 3
[0065] This embodiment provides a method for preparing a dual-conductive cathode active material, which is basically the same as the steps of Embodiment 1, except that in step (1), the mass of N-methylpyrrolidone is 600 g, the solid content of the polyamic acid / carbon nanotube dispersion is 0.54 wt%, the reaction temperature in step (2) is 400 °C, the reaction time is 15 min, and the mass ratio of the coating layer to the lithium-rich manganese-based material is 1:20; in the coating layer, the mass ratio of polyimide to carbon nanotubes is 1:1, and the thickness of the coating layer is 1 nm.
[0066] Example 4
[0067] This embodiment provides a method for preparing a dual-conductive cathode active material, which is basically the same as the steps of Embodiment 1, except that in step (1), benzidine disulfonic acid is replaced with 0.74 g of 3,5-bis(4-aminophenoxy)benzoic acid and 0.88 g of 1,3,5-tris(4-aminophenoxy)benzene, and the mass ratio of the coating layer to the lithium-rich manganese-based material is 1:4.5; in the coating layer, the mass ratio of polyimide to carbon nanotubes is 8:0.44, and the thickness of the coating layer is 9 nm.
[0068] Example 5
[0069] This embodiment provides a method for preparing a dual-conductive cathode active material, which is basically the same as the steps of Embodiment 1, except that in step (1), the dianhydride is replaced with 3,3',4,4'-benzophenone tetracarboxylic dianhydride with the same molar amount, and the solvent is replaced with N,N-dimethylformamide (DMF) with the same mass, and the mass ratio of the coating layer to the lithium-rich manganese-based material is 1:4.5; in the coating layer, the mass ratio of polyimide to carbon nanotubes is 3:0.5, and the thickness of the coating layer is 9 nm.
[0070] Example 6
[0071] This embodiment provides a method for preparing a dual-conductive cathode active material, which is basically the same as the steps of Embodiment 1, except that in step (1), the carbon nanotubes are replaced with single-arm carbon nanotubes, and the mass ratio of the coating layer to the lithium-rich manganese-based material is 1:5; in the coating layer, the mass ratio of polyimide to carbon nanotubes is 7:1, and the thickness of the coating layer is 8 nm.
[0072] Embodiment 7
[0073] This embodiment provides a method for preparing a dual-conductive cathode active material, comprising the following steps:
[0074] (1) Add 0.055 g of diphenylsulfone dianhydride, 0.033 g of bis(4-aminophenyl)sulfide, and 0.088 g of double-walled carbon nanotubes to 8.6 g of dimethyl sulfoxide, and react for 2 h under a nitrogen atmosphere to obtain a polyamic acid / carbon nanotube dispersion with a solid content of 2.01 wt%;
[0075] (2) Add 176 g of lithium-rich manganese-based material (0.8Li2MnO3·(0.2LiNiO2)) to the above polyamic acid / carbon nanotube dispersion, stir for 50 min, filter, dry, grind, sieve, and then perform thermal imidization treatment at 350 °C for 100 min to obtain; wherein, the mass ratio of the coating layer to the lithium-rich manganese-based material is 0.1:100; in the coating layer, the mass ratio of polyimide to carbon nanotubes is 1:1, and the thickness of the coating layer is 0.1 nm.
[0076] Embodiment 8
[0077] This embodiment provides a method for preparing a dual-conductive cathode active material, comprising the following steps:
[0078] (1) Add 5.2 g of bisphenol A dianhydride, 2.7 g of 2,2'-bis(3-amino-4-hydroxyphenyl)propane, and 0.079 g of carboxylated multi-walled carbon nanotubes to 152 g of N-N-dimethylacetamide, and react for 24 h under a nitrogen atmosphere to obtain a polyamic acid / carbon nanotube dispersion with a solid content of 4.99 wt%;
[0079] (2) Add 8 g of lithium-rich manganese-based material (0.8Li2MnO3·(0.2LiNiO2)) to the above polyamic acid / carbon nanotube dispersion, stir for 30 min, filter, dry, grind, sieve, and then perform thermal imidization treatment at 250 °C for 200 min to obtain; wherein, the mass ratio of the coating layer to the lithium-rich manganese-based material is 1:1; in the coating layer, the mass ratio of polyimide to carbon nanotubes is 10:0.1, and the thickness of the coating layer is 20 nm.
[0080] Embodiment 9
[0081] This embodiment provides a method for preparing a dual-conductive cathode active material, which includes the following steps:
[0082] (1) Add 2.18 g of pyromellitic dianhydride, 3.36 g of amino-terminated polydimethylsiloxane, and 1.48 g of amino-functionalized multi-walled carbon nanotubes to 169 g of N-methylpyrrolidone, and react for 15 h under a nitrogen atmosphere to obtain a polyamic acid / carbon nanotube dispersion with a solid content of 4 wt%;
[0083] (2) Add 140.4 g of lithium-rich manganese-based material (0.8Li2MnO3·(0.2LiNiO2)) to the above polyamic acid / carbon nanotube dispersion, stir for 70 min, filter, dry, grind, and sieve, and then perform thermal imidization treatment at 200 °C for 300 min to obtain; wherein, the mass ratio of the coating layer to the lithium-rich manganese-based material is 0.25:5; in the coating layer, the mass ratio of polyimide to carbon nanotubes is 3:0.8, and the thickness of the coating layer is 1 nm.
[0084] Example 10
[0085] This embodiment provides a method for preparing a dual-conductive cathode active material, which includes the following steps:
[0086] (1) Add 4.44 g of hexafluoroisopropyl phthalic anhydride, 2.39 g of 5,5'-oxybis(2-aminophenol), and 0.41 g of single-arm carbon nanotubes to 235 g of dimethyl sulfoxide, and react for 9 h under a nitrogen atmosphere to obtain a polyamic acid / carbon nanotube dispersion with a solid content of 3 wt%;
[0087] (2) Add 48.3 g of lithium-rich manganese-based material (0.8Li2MnO3·(0.2LiNiO2)) to the above polyamic acid / carbon nanotube dispersion, stir for 90 min, filter, dry, grind, and sieve, and then perform thermal imidization treatment at 400 °C for 50 min to obtain; wherein, the mass ratio of the coating layer to the lithium-rich manganese-based material is 7.5:50; in the coating layer, the mass ratio of polyimide to carbon nanotubes is 5:0.3, and the thickness of the coating layer is 6 nm.
[0088] Comparative Example 1
[0089] This comparative example provides a method for preparing a cathode active material, which is basically the same as the steps of Example 1, except that in step (1), adding hydroxylated multi-walled carbon nanotubes is omitted.
[0090] Comparative Example 2
[0091] This comparative example provides a method for preparing a dual-conductive cathode active material, which is basically the same as the steps of Example 1, except that the mass of 4,4'-biphenyl ether dianhydride is 14.93 g, the mass of benzidine disulfonic acid is 15.91 g, and the mass ratio of polyimide to carbon nanotubes is 7:0.09.
[0092] Comparative Example 3
[0093] This comparative example provides a method for preparing a dual-conductive cathode active material, which is basically the same as the steps of Example 1, except that the mass of 4,4'-biphenyl ether dianhydride is 0.137 g, the mass of benzidine disulfonic acid is 0.146 g, and the mass ratio of polyimide to carbon nanotubes is 7:10.
[0094] Comparative Example 4
[0095] This comparative example provides a method for preparing a dual-conductive cathode active material, which is basically the same as the steps of Example 1, except that the hydroxylated multi-walled carbon nanotubes are replaced with nano-scale conductive carbon.
[0096] Experimental Example 1
[0097] The dual-conductive cathode active materials prepared in the above Examples 1-3 were subjected to transmission electron microscopy tests, and the results are shown in Figures 1 - 3 As shown, it can be seen from the figure that the composition, content, and concentration of polyimide / carbon nanotubes on the surface of the dual-conductive cathode active material affect the microscopic thickness of the coating layer.
[0098] The dual-conductive cathode active material prepared in Example 2 and the lithium-rich manganese-based material were subjected to scanning electron microscopy tests, and the results are shown in Figures 4 - 5 As shown, it can be seen from the figure that the surface of the lithium-rich manganese-based material is smooth, the surface of the cathode active material is rough, and the carbon nanotubes are tubular structures, proving that there is an obvious polyimide and carbon nanotube coating layer on the surface of the dual-conductive cathode active material.
[0099] The dual-conductive cathode active material prepared in Example 1 and the lithium-rich manganese-based material were subjected to XRD tests, and the results are shown in Figure 6 As shown, it can be seen from the figure that the dual-conductive cathode active material and the lithium-rich manganese-based material have similar crystal structures, and the dual-conductive cathode active material shows a characteristic peak of carbon nanotubes at (002).
[0100] Experimental Example 2
[0101] The cathode active materials prepared in the above examples and comparative examples were made into test batteries for performance testing, which specifically included the following steps:
[0102] The cathode active materials, polyvinylidene fluoride, and conductive carbon black prepared in Examples 1-10 and Comparative Examples 1-4 were mixed and dispersed in N-methylpyrrolidone in a mass ratio of 8:1:1 to obtain a cathode slurry; then the cathode slurry was coated on the surface of an aluminum foil current collector and dried in a vacuum oven at 80°C for 12 h, and then cut into circular electrodes with a diameter of 12 mm. Using the circular electrode as the working electrode, metallic lithium as the counter electrode, Celgard 2400 membrane as the separator, and 1 M lithium hexafluorophosphate (LiPF6) dissolved in ethylene carbonate (EC) / dimethyl carbonate (DMC) (the volume ratio of ethylene carbonate to dimethyl carbonate is 1:1) as the electrolyte, the 2032-type button cell was assembled in a glove box filled with Ar atmosphere. After standing for 12 h, the electrochemical performance test was carried out in the voltage range of 2 V-4.6 V. The results are shown in Table 1 below. The dual-conductive cathode active material and lithium-rich manganese-based material prepared in Example 2 had a charge-discharge curve after 1 cycle at a current density of 0.1 C (1 C = 200 mAh g -1 ) as shown in Figure 7 . The results of the rate performance test are shown in Figure 8 .
[0103] Table 1 Performance test results of the cathode active materials prepared in each example and comparative example
[0104]
[0105] As can be seen from the above table, the components, contents, and thicknesses of the polyimide / carbon nanotube coating layers prepared in Examples 1-10 affect the rate performance, initial Coulombic efficiency, discharge specific capacity, and capacity retention rate after 100 cycles of the dual-conductive cathode active material; the initial Coulombic efficiency and discharge specific capacity of Comparative Example 1 are significantly lower than those of the Examples because the polyimide single coating layer is an electron-conductive insulator, which hinders the electron migration of the cathode active material; the initial Coulombic efficiency, discharge specific capacity, and capacity retention rate of Comparative Example 2 are significantly lower than those of the Examples because the polyimide / multi-walled carbon nanotube coating layer has both ion-conductive and electron-conductive properties. Controlling the mass ratio of polyimide to carbon nanotubes at 1-10:0.1-1 can ensure that the coating layer has an appropriate thickness, which can not only ensure unobstructed ion / electron migration of the dual-conductive cathode active material but also stabilize the surface structure of the dual-conductive cathode active material, facilitating the exertion of the electrochemical performance of the dual-conductive cathode active material; the initial Coulombic efficiency, discharge specific capacity, and capacity retention rate of Comparative Example 3 are significantly lower than those of the Examples because an excessive amount of carbon nanotubes causes serious clustering and caking phenomena, resulting in a non-uniform coating layer and an unsmooth conductive network; the initial Coulombic efficiency, discharge specific capacity, and capacity retention rate of Comparative Example 4 are significantly lower than those of the Examples because compared with nano-scale conductive carbon black, carbon nanotubes have good electron conductivity, and their fibrous structure can form a continuous conductive network in the matrix material. After adding carbon nanotubes, the matrix material has higher toughness, can improve the exfoliation caused by the volume change of the material during charge and discharge, and can increase the cycle life. Carbon nanotubes can significantly improve the penetration ability of the electrolyte in the matrix material and promote ion conduction; while nano-scale conductive carbon black is prone to agglomeration due to its high surface energy, significantly increases the viscosity of the coating system, is prone to side reactions, resulting in uneven dispersion and difficult processing, which affects the electrochemical performance.
[0106] From Figure 7 it can be seen that at a voltage of 2.0V-4.6V and a current density of 0.1C, the discharge specific capacity of Example 2 is 236.6 mAh·g -1 , and the initial Coulombic efficiency reaches 86.7%, which is higher than the discharge specific capacity and initial Coulombic efficiency of the lithium-rich manganese-based material; from Figure 8 it can be seen that at a voltage of 2.0V-4.6V, the discharge capacities of the cathode active material and the lithium-rich manganese-based material prepared in Example 2 show a decreasing trend with the increase of the current density. The discharge capacity of the cathode active material prepared in Example 2 is significantly higher than that of the lithium-rich manganese-based material, indicating that the cathode active material prepared in Example 2 has good rate performance.
[0107] Obviously, the above embodiments are merely examples for clear illustration and not limitations on the implementation manners. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to enumerate all the implementation manners here. And the obvious changes or modifications derived therefrom still fall within the protection scope of the present invention.
Claims
1. A dual-conductive cathode active material, comprising a matrix material and a coating layer coated on the outer surface of the matrix material, wherein the matrix material is a lithium-rich manganese-based material, characterized in that, The coating layer comprises polyimide and carbon nanotubes; The mass ratio of the polyimide to the carbon nanotubes is 1 - 10:0.1 - 1.
2. The dual-conductive positive electrode active material according to claim 1, wherein The mass ratio of the coating layer to the matrix material is 0.1 - 10:1 - 100.
3. The dual-conductive positive electrode active material according to claim 1 or 2, characterized in that, The thickness of the coating layer is 0.1 nm - 20 nm.
4. The dual-conductive positive electrode active material according to claim 1 or 2, characterized in that, The carbon nanotubes include at least one of single-walled carbon nanotubes, double-walled carbon nanotubes, hydroxylated multi-walled carbon nanotubes, carboxylated multi-walled carbon nanotubes, and aminated multi-walled carbon nanotubes; And / or, the chemical formula of the lithium-rich manganese-based material is xLi2MnO3·(1 - x)LiMO2; wherein, 0 ≤ x ≤ 1, and M includes at least one of Ni, Co, and Mn.
5. A method for preparing the dual-conductive cathode active material according to any one of claims 1-4, characterized in that, It includes the following steps: (1) React carbon nanotubes with a dianhydride, a diamine, and / or a polyamine to obtain a polyamic acid / carbon nanotube dispersion; (2) Place the lithium-rich manganese-based material in the polyamic acid / carbon nanotube dispersion, stir, filter, dry the filter residue, and obtain it after heat treatment.
6. The preparation method of the bipolar cathode active material according to claim 5, characterized in that, The molar ratio of the dianhydride to the diamine and / or polyamine is 1:0.95 - 1.05; And / or, the proportional relationship between the dianhydride and the carbon nanotubes is 0.0001 mol - 0.01 mol:0.05 g - 1.5 g; And / or, the proportional relationship between the dianhydride and the lithium-rich manganese-based material is 0.0001 mol - 0.01 mol:8 g - 180 g.
7. The preparation method of the bipolar positive electrode active material according to claim 5 or 6, characterized in that, The solid content of the polyamic acid / carbon nanotube dispersion is 0.01 wt% - 10 wt%; And / or, a solvent is further included in step (1), and the solvent includes at least one of N-N-dimethylformamide, N-N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; And / or, the proportional relationship between the dianhydride and the solvent is 0.0001 mol - 0.01 mol:8 g - 960 g.
8. The preparation method of the bipolar positive active material according to claim 5 or 6, characterized in that, The reaction time is 2 h - 24 h; And / or, the stirring time is 10 min - 120 min; And / or, the temperature of the heat treatment is 200°C - 400°C, and the treatment time is 15 min - 300 min.
9. The preparation method of the bipolar positive active material according to claim 5, wherein The dianhydride includes at least one of pyromellitic dianhydride, biphenyl dianhydride, hexafluoroisopropyl phthalic anhydride, 4,4'-biphenyl ether dianhydride, 3,3',4,4'-terphenyl bisether tetracarboxylic dianhydride, diphenyl sulfide dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, and bisphenol A type dianhydride; And / or, the diamine includes at least one of benzidine disulfonic acid, bis(4-aminophenyl) sulfide, 5,5'-diamino-2,2'-hydroxy-diphenyl, 2,2'-bis(3-amino-4-hydroxyphenyl) propane, 3,3'-diamino-4,4'-dihydroxybiphenyl, 3,5-diaminobenzoic acid, 3,5-bis(4-aminophenoxy) benzoic acid, 5,5'-oxybis(2-aminophenol), and aminopropyl double-capped polydimethylsiloxane; And / or, the polyamine includes at least one of 1,3,5-tris(4-aminophenoxy)benzene, 1,3,5-tris(4-aminophenyl)benzene, 1,3,5-tris(2-amino-4-carboxyphenyl)benzene, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, and 1,3,5-triaminobenzene.
10. A lithium-ion battery, comprising a positive electrode, the positive electrode including a positive electrode active layer, and the positive electrode active layer including a positive electrode active material; characterized in that, The positive electrode active material includes the dual-conductive positive electrode active material according to any one of claims 1-4, or the dual-conductive positive electrode active material prepared by the preparation method according to any one of claims 5-9.
Citation Information
Cited By
Lithium-rich manganese-based positive electrode material and preparation method thereof
CN120784336A